Sikap terhadap Iklan dan Sikap terhadap Merek sebagai Variabel Perantara dalam Iklan Komparatif: Pengujian Spesifikasi Empat Alternatif Model - Wijayanti, Rindra Tri Wahyu; Junaedi, Shellyana (Kajian Manajemen dan Bisnis, 2011)
High competition sale that make company do sale promotion to interest consumers, and one of them by means of advertising media. It is need a message interest for consumers with comparative advertising applied. Advertising comparative in TV is a phenomenon, so the research is to measure advertising comparative used by model development, Four Alternative Specifications of The Mediating Role of AAD. The research used survey method with distributed quesionare to 257 respondents. Processing data used by Structural Equation Model (SEM) analysis with AMOS Program Version 6.0. In this research used primer data and collective sample used non probability sampling technique with purposive sampling method.